﻿O uso de modelos no ensino de química: uma investigação acerca dos saberes construídos durante a formação inicial de professores de Química da UFRN - Lima, Analice de Almeida (2007)
﻿In the past twenty years, there has been a significant increase of researches about teacher s professionalization. In that context, the investigations concerning teacher s knowledge represent an important contribution, as they aim to identify and to rescue the base of knowledge that sustains the teacher s profession. In particular, the reflections and propositions of Lee Shulman have been constitute a fundamental subsidy to the teacher s professionalization in the sense of harnessing the pedagogic knowledge to the content s knowledge, establishing the pedagogic knowledge of the content that characterizes and differentiates the teacher and the bachelor in a certain field of knowledge. Among the indispensable knowledge for the Chemistry teacher's professional practice, in this research we have pointed out the pertinence of the knowledge on the use of models in Chemistry classes in the middle and high school. Those knowledges regard the comprehension of students concerning the understanding and models elaborated in science and the models implemented in the Chemistry teaching, as well as the abilities to plan didactic situations that use models. In this research, we aimed to identify the contributions and barriers during the Chemistry teacher education, in UFRN, in relation to the construction of knowledge that subsidize training teachers in the elaboration of teaching activities that involve the use of models. The investigation was accomplished in UFRN, in the Course of Degree in Chemistry, along with 13 student teachers that studied the subject Practice of Chemistry Teaching. For this research, the following instruments were used: questionnaires with open and closed questions, elaboration of a plan of activities for the Chemistry teaching and an interview to answer the established study s questions. The data was analyzed in an established criteria, classified and tabled. The results showed that the student teachers representations regarding scientific knowledge contemplated, among other topics, the idea of a method for his/her construction. In some cases, the models role was emphasized in that construction, as well as the social dimension in the validation of that knowledge. The scientific models were highlighted by most of the student teachers, as a representation method to explain, understand and interpret the chemical phenomena. On the other hand, the didactic models stood out, in most of cases, as a method of aiding the Chemistry students of the Basic Education to understand the scientific models. The representations regarding those categories contemplated important aspects, although in a superficial way, reflecting the limitations of reflections during the formative process. In the elaboration of teaching activities that use models, difficulties were evidenced, in the process of plan construction, relative to the didactic structure and to the proposition of activities that contemplated models, although the student teachers have mobilized different elements regarding the pedagogic knowledge of the content. Such verifications evidence the urge for the teacher development programs to promote changes in the teacher education in order to propitiate, during this process, reflections, discussions and propositions of activities regarding categories highlighted in this research, contributing to the construction of initial elements regarding the pedagogic knowledge of the content that will be developed throughout teaching, therefore corroborating to the teacher s professionalization